2005
DOI: 10.1007/s10346-005-0004-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of some spatial and temporal issues in landslide initiation within the Río Aguas Catchment, South–East Spain

Abstract: A research programme underway in south-east Spain has the overall aim of developing a long-term landscape evolution model for the Tertiary depositional basins that lie within the eastern part of the Betic cordillera. As part of the work it has become apparent that there are multiple natural hazards to development in the region, and the nature and distribution of these is presently under investigation. For one hazard, namely landsliding, a database of over 300 cases has been compiled within one defined 425 km 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…This uses a hierarchical approach which allows a large area to be broken down systematically into smaller units depending on geology, hydrology and geomorphology. Eyles (1983) used the approach for mapping glacial terrains and identified the genetic relationship between landforms and the processes and materials involved in their development; Griffiths et al (2005) established that terrain systems mapping can provide an effective tool in the investigation of landslide distributions at a regional scale. According to the Australian Geomechanics Society (2000) identification of landslides requires an understanding of slope processes and the relationship of these to geomorphology, geology, hydrogeology, climate and vegetation.…”
Section: Landslide Domainsmentioning
confidence: 99%
“…This uses a hierarchical approach which allows a large area to be broken down systematically into smaller units depending on geology, hydrology and geomorphology. Eyles (1983) used the approach for mapping glacial terrains and identified the genetic relationship between landforms and the processes and materials involved in their development; Griffiths et al (2005) established that terrain systems mapping can provide an effective tool in the investigation of landslide distributions at a regional scale. According to the Australian Geomechanics Society (2000) identification of landslides requires an understanding of slope processes and the relationship of these to geomorphology, geology, hydrogeology, climate and vegetation.…”
Section: Landslide Domainsmentioning
confidence: 99%
“…This evidence suggests a cyclicity in dominant processes in this setting, which is not inconsistent with that interpreted for the much drier Henry Mountains badlands by Howard (1997). Mass movements have been noted on large scales in badlands in Alberta (De Lugt and Campbell, 1992), Italy (Piccarreta et al, 2006;Ciccacci et al, 2008) and Spain (Griffiths et al, 2005). As well as contributing to large-scale evolution, mudflows have also been demonstrated in extreme events on a within-slope scale (Oostwoud Wijdenes and Ergenzinger, 1998; Ciccacci et al, 2008;Godfrey, Everitt and Martín Duque, 2008).…”
Section: Processes and Rates Of Badland Evolutionmentioning
confidence: 75%
“…Farifteh and Soeters (2006) suggested that the size and spacing of joints and faults in basilicata was responsible for the patterns of biancane (small, isolated) rather than calanchi (large, gullied) badland systems. Griffiths et al (2005) noted that landslides in badlands in the Aguas basin in southern Spain were more likely to occur on specific lithological boundaries (e.g. 39 % of all landslides where multiple lithologies were present occurred where the lower unit was a calcareous mudstone).…”
Section: Rcmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the Landslide Domain Map incorporated a land system mapping method (Engineering Group Working Party 1982;Griffiths et al 2005;Guzzetti 2005;Pasuto and Soldati 1999;Savigear 1965;Styles et al 1984;Wilshusen 1979). A terrain system covering a large area can be subdivided into a number of defining terrain facets, which in turn may be further broken down to terrain elements (Tab.…”
Section: Land Systems Mappingmentioning
confidence: 99%